The Plasma Environment Surrounding the Reiner Gamma Magnetic Anomaly. Issue 9 (26th August 2021) - Deca, J.; Poppe, A. R.; Divin, A.; Lembège, B.
Abstract: Reiner Gamma is a prime target for low‐orbiting spacecraft or even surface‐landed missions in the near future. The region hosts a prominent lunar swirl that is co‐located with a strong and well‐structured magnetic anomaly. We simulate and discuss Reiner Gamma's near‐surface plasma environment at different altitudes above the lunar surface using the fully kinetic particle‐in‐cell code iPIC3D. The input magnetic field model is based on orbital‐altitude observations from the Kaguya and Lunar Prospector missions. We develop eight simulation cases, representing the distinct plasma regimes. Reiner Gamma is exposed to along a typical orbit, including different solar wind incidence angles and the magnetosheath crossing. We show that the plasma environment is vastly different at different altitudes and depends critically on the upstream plasma parameters, consistent with the predictions of the solar wind standoff model. Our work helps to define measurement requirements for a possible future low‐orbiting or lander mission to the Reiner Gamma area or similarly magnetized regions of the lunar surface. Plain Language Summary: The Reiner Gamma region on the lunar surface hosts a set of brightness variations, or "swirls, " that are co‐located with a prominent crustal magnetic field. Recently, it has been identified as one of the prime locations to be visited by one of NASA's next lunar missions. Here, we analyze the distinct plasma regimes that such a mission may encounter along its trajectory, such as the Moon's crossing through the Earth's magnetosheath and a set of different solar wind directions. We simulate the electron, proton, and H e 2 + dynamics with computational particles and include the Reiner Gamma magnetic field using a model developed from Kaguya and Lunar Prospector measurements. We find that the plasma environment is vastly different at different altitudes and depends critically on the upstream plasma parameters. Our models are essential to help define the measurement requirements for future endeavors to magnetized regions on the lunar surface, such as Reiner Gamma. Key Points: Fully kinetic self‐consistent simulations of the Reiner Gamma plasma environment The plasma environment is vastly different at different altitudes and depends critically on the upstream plasma Our work helps to define measurement requirements for future missions to magnetized regions of the lunar surface